SISTEM INFORMASI MANAJEMEN PRAKTIK KERJA LAPANGAN DAN TUGAS AKHIR - Aslam Fatkhudin; Ashshohwah Mulia Ardil Pamungkas (Jurnal Surya Informatika: Membangun Informasi dan Profesionalisme, 2017)
Work Practice (PKL) and Final Project (TA), is a subject that must be taken by students in the final semester, the course is used as one of the requirements for completing the course in the Diploma III (D3). In the process of implementation, there are several processes and grooves that must be passed from the provision of information, the registration process, monitoring of implementation and the process of giving value to students who do field work practices. In this study, expected to assist the Politeknik Muhammadiyah Pekalongan in the process of management of Field Work Practice (PKL) and Final Project (TA).